THERMAL PERFORMANCE FOR HYDROPONIC MAIZE FODDER PRODUCTION - SANJAY KUMAR SINGH,; AMIT KUMAR PATIL,; SHESHRAO KAUTKAR,; P. N. DWIVEDI, (The Bioscan, 2021)
It is difficult to fulfill the daily green fodder requirement of farm animals throughout the year in the era of global warming. The study focused on the development of an evaporative cool hydroponic chamber (ECHC) to grow green fodder in summer season. It consists of a double layered wall, filler material inside the wall, fogging system, drip system for water application and a shading curtain. The thermal performance of chamber was evaluated in terms of humidifying performance and its utility for production of hydroponic maize. Combined effect of evaporative cooling and misting system maintained the daily average temperature and relative humidity (RH) in the range of 28.6-30.2ºC and 65.2-75.1% respectively under ECHC as compared to temperature and RH of ambient in the range of 28.5-41.4º C and 37–77% respectively.